2017
DOI: 10.15580/gjas.2017.2.032317044
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Anti-Nutritional Composition of Crop Residues and Kitchen Wastes Fed to Small Ruminants in Choba, Port Harcourt

Abstract: The study was carried out to determine the nutrient composition, anti-nutritional factors and mineral content of crop residues and kitchen wastes fed to small ruminants in Choba and to ascertain the best crop residues and kitchen wastes suitable to these animals. The samples of crop residues and kitchen wastes commonly fed to small ruminants were collected from farms, home of farmers and restaurants around the study area. They were dried and analysed for moisture content, crude protein, crude fibre, ether extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
1
1
1
Order By: Relevance
“…Peel and Pineapple Skin Table 2 illustrated the antinutritonal content of our sample. Study on the antinutritional factor in banana peel revealed that phytic acid content was 0.79 mg/100 g. This value was higher from Anwahge et al [22] and Adenji et al [37] which both found the level of the phytate in their sample was 0.28 mg/100 g. Maniyan et al [38] also discovered lower phytic acid in their sample, 0.40 mg/100 g. We found phytic acid in pineapple skin was 0.28 mg/100 g. This amount is lower than reported by Feumba et al [29] (1.99 mg/100 g) but higher than the study done by Ukanwonko and Nwachuku [39] (0.09 mg/100 g). Determination of tannic acid in banana peel waste discovered the content of this compound was 0.083 mg/100g.…”
Section: Antinutritional Content Of Bananacontrasting
confidence: 55%
See 1 more Smart Citation
“…Peel and Pineapple Skin Table 2 illustrated the antinutritonal content of our sample. Study on the antinutritional factor in banana peel revealed that phytic acid content was 0.79 mg/100 g. This value was higher from Anwahge et al [22] and Adenji et al [37] which both found the level of the phytate in their sample was 0.28 mg/100 g. Maniyan et al [38] also discovered lower phytic acid in their sample, 0.40 mg/100 g. We found phytic acid in pineapple skin was 0.28 mg/100 g. This amount is lower than reported by Feumba et al [29] (1.99 mg/100 g) but higher than the study done by Ukanwonko and Nwachuku [39] (0.09 mg/100 g). Determination of tannic acid in banana peel waste discovered the content of this compound was 0.083 mg/100g.…”
Section: Antinutritional Content Of Bananacontrasting
confidence: 55%
“…This value was between 0.04 g/ml discovered by Maniyan et al [38] and 0.28 mg/100 g found by Anhwange et al [22]. We found much lower value for tannic acid in our pineapple skin sample with respect for those reported by Ukanwonko and Nwachuku [39] (5.02 mg/100 g). An experiment undertaken by Sabahelkhier et al [40] on chemical composition and effect of maturity stage on protein fractionation, discovered that level of tannic acid for 45 maturity days was 4.5 mg/100 g. Different cultivar and botanical factor of planted banana may contribute to the variability of the results.…”
Section: Antinutritional Content Of Bananasupporting
confidence: 50%
“…During solid-state fermentation (SSF), the increased nutrition values were due to bioconversion of substrate that had been degraded by fungal enzymes (Thana et al 2019). Maize cob contains 5.22% protein, anti-nutrients, such as saponin (2.09%), tannin (0.03%) and phytate (0.72%) (Ukanwoko and Nwachukwu 2017), cellulose (27.71%) and hemicellulose (38.78%) but also contain a significant amount of lignin (9.4%) (Shinners et al 2007), calcium (17.19 mg/100 g), potassium (375.25 mg/100 g), sodium (129.19 mg/100 g) (Abubakar et al 2016) and antioxidant activity of 0.3-10 µmol/ gdw (Nawaz et al 2018). Maize husk is the leafy outer covering of an ear of maize (corn) as it grows on the plant (Wikipedia 2020).…”
Section: Introductionmentioning
confidence: 99%